BL_GERICHTE 720 12 360 / 42 vom 8. Juni 1999 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 7. März 2013 (720 12 360 / 42) - BL Gerichte (1999)
Hilflosenentschädigung